2018
DOI: 10.2147/cia.s149920
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function as indicated by heart rate deceleration capacity and deceleration runs in type 2 diabetes patients with or without essential hypertension

Abstract: PurposeSympathovagal imbalance is a common underlying disorder in hypertension and diabetes. This study characterized autonomic nervous system function, indicated by heart rate deceleration capacity (DC) and deceleration runs (DRs), in patients with type 2 diabetes mellitus (T2DM), with or without concomitant essential hypertension.Subjects and methodsWe recruited 50 healthy subjects, 50 patients with T2DM, and 95 with T2DM and essential hypertension. DC, DRs (DR2, DR4, and DR8, ie, episodes of 2, 4, or 8 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…[29] Studies have already demonstrated the reduced HRV could be regarded as early indicators of cardiac autonomic dysfunction. [7,30,31] This study found that vitamin D levels of T2DM patients in the deficiency group were associated with reduced SDNN, ASDNN, pNN50, LF, HF, SDANN, and rMSSD. Meanwhile, the LF/HF in the deficiency group was significantly higher than those in the sufficiency group.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[29] Studies have already demonstrated the reduced HRV could be regarded as early indicators of cardiac autonomic dysfunction. [7,30,31] This study found that vitamin D levels of T2DM patients in the deficiency group were associated with reduced SDNN, ASDNN, pNN50, LF, HF, SDANN, and rMSSD. Meanwhile, the LF/HF in the deficiency group was significantly higher than those in the sufficiency group.…”
Section: Discussionmentioning
confidence: 66%
“…[29] Studies have already demonstrated the reduced HRV could be regarded as early indicators of cardiac autonomic dysfunction. [7,30,31]…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Increased RHR leads to increased secretion of several inflammatory cytokines, such as highsensitivity C-reactive protein, fibrinogen, and interleukin-6, implying that the general population with high RHR is in a subclinical inflammatory state. [17][18][19][20] Our observational study was conducted among a community-based population and included individuals with no obvious symptoms of discomfort; additionally, all data were from routine physical examinations. Most RHR values in our study population were in the range 57 to 80 beats/minute.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Increased RHR leads to increased secretion of several inflammatory cytokines, such as high-sensitivity C-reactive protein, fibrinogen, and interleukin-6, implying that the general population with high RHR is in a subclinical inflammatory state. 17 20 …”
Section: Discussionmentioning
confidence: 99%
“…Analyses of heart rate and heart rate variability (HRV) have broad biomedical applications ranging from diagnosis of cardiovascular diseases based on arrhythmias [45][46][47] to noninvasive assessment of autonomic nervous system (ANS) activities [48][49][50][51][52]. Experimental evidences for the association between lethal arrhythmias and sympathovagal imbalance have been reported [53][54][55][56][57] and changes in HRV have been associated with derangements in the neural activity of cardiac origin following myocardial infarction [58,59] as well as with the onset of diabetic neuropathy [60,61]. Furthermore, a previous work [62] demonstrated that PPG variability (PPGV) could be used as an alternative to HRV by comparing the similarity between PPGV and HRV.…”
Section: B Heart Rate Preservation In Generated Ppg and Potential Applications To Data Augmentationmentioning
confidence: 99%